Design An Automatic Shuttlecock Output Device Using An Arduino Based Servo Motor - Fadly Hikmatus Sholichin; Syamsudduha Syahrorini; Arief Wisaksono (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
Badminton is a sport that uses a racket tool  as a bat and shuttlecock as a bat and the slop itself is a container for placing  a shuttlecock  with a length of 37 cm. Badminton is a sport that the majority of many enthusiasts. And began to emerge associations of badminton players who were then trained by coaches to then make a profession or their own expertise. In general, shuttlecocks are  removed manually and do not know whether the contents of the slop are exhausted or still filled. Therefore,  automatic shuttlecock  storage devices can make it easier for coaches to provide training to students who are in the association of badminton players. This tool can store  shuttlecocks and remove shuttlecocks automatically which are stored in a dislop containing 12 seeds, the microcontroller used is Arduino Uno, the servo motor is used  to remove the shuttlecock that has a dislop and if the  shuttlecock is not filled then the Servo Motor does not run or open to remove the   shuttlecock  so that the slop must be replenished, then the HC-SR04 Sensor above the slop functions as a device that detects whether  the shuttlecock is still there, then there is the  ISD1820 Sensor which functions as an alarm to notify by voice that  the shuttlecock is up and time to refill, then a tripod as the foundation for  this automatic shuttlecock  storage device. The result of this research test is that 12 shuttlecock seeds  were successful. In this case, it is hoped that this research can help and facilitate coaches in training in a badminton player association on a large scale as well as efficiently knowing the exhaustion of shuttlecocks.